Direct economic burden of acute coronary syndromes in the Portuguese National Health Service—facts and trends between 2002 and 2022 - Madeira, Francisco; Martins, Carla; Viegas, Susana; Timóteo, Ana Teresa; Loureiro, Fátima; Perelman, Julian (Frontiers in Public Health, 2025)
AimWe estimated the average direct cost per Acute Coronary Syndromes (ACS) in-patient episodes by diagnosis, namely ST-elevation myocardial infarction (STEMI), non-ST elevation myocardial infarction (NSTEMI), unstable angina (UA), and undetermined AMI (Acute Myocardial Infarction). We also analyzed the changes in direct costs over time between 2002 and 2022, and the total direct economic burden of ACS hospitalizations for the Portuguese National Health Service (NHS).MethodsWe used the Portuguese Registry of Acute Coronary Syndromes (61,440 ACS hospitalizations), a cohort of people with ACS, recruited and followed from first hospitalization. A direct cost analysis was conducted. As resources, we considered health professional working hours, non-medical resources used during in-patient stays, laboratory and diagnostic tests, interventional cardiology procedures, pharmaceuticals, hospitalization-related complications, rehabilitation services, and death costs. A multivariate analysis was performed to identify the main cost determinants.ResultsThe average cost per ACS patient from 2002 to 2022 was 6,280.79 €. A significantly higher average cost was observed among patients diagnosed with STEMI of 3,853.26€ (95% confidence interval [CI] 3,690.87 to 4,015.65€), among NSTEMI patients of 1,308.91 € (95% CI 1,173.52 € to 1,444.30 €), and among patients who died during the hospitalization of 12,017.64€ (95% CI 11,232.21 € to 12,803.08 €). Over time, cost trends fluctuated, increasing until 2011 and then gradually decreasing until 2022, apart from 2020. Considering the total universe of 294,307 ACS-hospitalizations, the Portuguese NHS incurred a direct economic burden of 1,831 million euros over the complete period, with total annual costs averaging 87,203,851 €, representing on average 0.93% of the NHS annual health expenditure.ConclusionACS represent a significant direct cost and economic burden for the NHS.